The first 6 months of HIV-SARS-CoV-2 coinfection: outcomes for 6947 individuals. Issue 1 (January 2021) - Johnston, Rowena
Abstract : Purpose of review: The aim of this review is to summarize the clinical outcomes of people living with HIV (PWH) coinfected with SARS-CoV-2 during the first six months of the COVID-19 pandemic. Recent findings: Several reports from single centers have described increased, decreased, or no difference in outcomes of COVID-19 in PWH. These studies have come from a range of locations, each with different underlying HIV prevalence and access to various antiretroviral therapy (ART) regimens. Differences in healthcare quality, access and policies may also affect reported outcomes in PWH across different locations, making interpretation of results more challenging. Meanwhile, different components of ART have been proposed to protect against SARS-CoV-2 acquisition or disease progression. Summary: The current review considers 6 months of data across geographic regions with a range of healthcare quality and access and ART regimens to generate a wider view of COVID-19 outcomes in PWH. Taken together, these studies indicate that HIV infection may be associated with increased risk of COVID-19 diagnosis, but comorbidities appear to play a larger role than HIV-specific variables in outcomes of COVID-19 among PWH. ART does not appear to protect from COVID-19 disease acquisition, progression or death.